2011
DOI: 10.1088/0031-9155/56/7/024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of early stage cartilage degradation using diffuse reflectance near infrared spectroscopy

Abstract: Interest in localized and early stage treatment technologies for joint conditions such as osteoarthritis is growing rapidly. It has therefore become important to develop objective measures capable of characterizing the earliest (non-visible) changes associated with degeneration to aid treatment procedures. In addition to assessing tissue before treatment, it is further important to develop an effective, non-destructive means of monitoring post-treatment tissue healing, and of providing the high-quality data ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 14 publications
2
28
0
1
Order By: Relevance
“…The most relevant changes were observed in the long NIR wavelength region where differences were observed at 7100 cm ) was reported by other authors to be associated with cartilage when pure bovine cartilage samples were analyzed using NIR spectroscopy [25][26][27]. These wavenumbers were associated with C-H combination and asymmetric first overtones of C-N-C stretch and N-H of proteins [25][26][27].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The most relevant changes were observed in the long NIR wavelength region where differences were observed at 7100 cm ) was reported by other authors to be associated with cartilage when pure bovine cartilage samples were analyzed using NIR spectroscopy [25][26][27]. These wavenumbers were associated with C-H combination and asymmetric first overtones of C-N-C stretch and N-H of proteins [25][26][27].…”
Section: Resultssupporting
confidence: 56%
“…These wavenumbers were associated with C-H combination and asymmetric first overtones of C-N-C stretch and N-H of proteins [25][26][27]. This region appears to be unique between the different tissues (e.g., fat, muscle, and skin) analyzed, indicating that differences in the absorbance values can be attributed to different protein and collagen ratios between tissues.…”
Section: Resultsmentioning
confidence: 94%
“…A discriminant analysis function was built based on clearly identifiable NIR absorption peaks in raw and 2nd derivative spectra. The function distinguished the normal cartilage from degraded tissue with greater than 95% accuracy (88). Potential of NIR spectroscopy for recognizing cartilage degradation in a rat OA model has also been studied.…”
Section: ¡1mentioning
confidence: 99%
“…Another series of studies by Brown demonstrated the correlation of NIR spectroscopic data to severity of cartilage degeneration in enzymatically degraded 11 and osteoarthritic tissues 12 .…”
Section: Introductionmentioning
confidence: 99%